1986
DOI: 10.1161/01.cir.73.5.885
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of electrocardiographic site of infarction after correction for enzymatic size of infarction.

Abstract: To assess whether the site of myocardial infarction is an independent prognostic indicator, the outcome of patients with anterior myocardial infarction was compared with that of patients with inferior infarction. A consecutive series of patients who had suffered their first myocardial infarction was analyzed (398 with anterior and 391 with inferior infarction). Patients with anterior myocardial infarction had a higher 1 year mortality than those with inferior infarction (18.3% vs 10.5%, p = .002). When patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(29 citation statements)
references
References 33 publications
4
24
1
Order By: Relevance
“…The findings of our study are in accordance with those usually reported in the literature: Hands et al 37 , comparing the evolution of patients with acute myocardial infarction of the anterior wall with that of patients with acute myocardial infarction of the inferior region, found a greater mortality in those patients with infarction of the anterior wall. Those authors stated that the location of infarction is an important prognostic indicator, independent of its magnitude, which is expressed by the peak in the creatine kinase levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of our study are in accordance with those usually reported in the literature: Hands et al 37 , comparing the evolution of patients with acute myocardial infarction of the anterior wall with that of patients with acute myocardial infarction of the inferior region, found a greater mortality in those patients with infarction of the anterior wall. Those authors stated that the location of infarction is an important prognostic indicator, independent of its magnitude, which is expressed by the peak in the creatine kinase levels.…”
Section: Discussionsupporting
confidence: 93%
“…The most frequent impairment of the left ventricular anterior wall and of the right ventricle in group B patients observed on the electrocardiogram is the major cause of the more severe condition of those patients 37,38 . That severity was equivalent to the severity of inferior acute myocardial infarction accompanied by impairment of the right ventricle and to the severity of anteroseptal infarction or the extensive infarction of the anterior wall, and, between them, no significant difference in regard to death exists (P = 0.4199).…”
Section: Discussionmentioning
confidence: 95%
“…5,8,14,15 These factors have included age, extent of left ventricular dysfunction, infarct size, and development of heart failure. [41][42][43][44] It is notable that most of these factors result in sympathetic activation, 1,2,13 which in turn is believed to lead to an adverse outcome. 1,2,21 In addition, it is known that the increased mortality associated with ant-AMI occurs during the first few hours after the onset of infarction.…”
Section: Graham Et Al Sympathetic Drive and Site Of Infarctionmentioning
confidence: 99%
“…It has been reported previously that LV function and the enzymatic size of infarction are independent predictors of prognosis after AMI. [3][4][5][6] Patients in group B had better preserved cardiac function with a smaller infarct than those in group P. Therefore, it was thought that in-hospital mortality in group B would tend to be lower despite the lower rate of primary PCI.…”
Section: Discussionmentioning
confidence: 99%